“NEW PERIPHERY” AS A FACTOR FOR STRENGTHENING THE POSITIONS OF ISRAEL IN THE MIDDLE EAST - Y. I. Kostenko (Vestnik MGIMO-Universiteta)
Since its establishment the State of Israel has sought alliances with non-Arab and non- Muslim countries and minorities in the Middle East, as well as Arab states geographically distant from the Arab-Israel conflict. The article presents and explains this regional orientation. It examines Israel's strategy of outflanking. The "periphery doctrine" was a grand strategy, meant to attain the major political-security goal of countering Arab hostility through relations with alternative regional powers and potential allies. This periphery strategy had been internalized to some extent in Israel's strategic thinking and it began to reappear after 2010, following a new era of Arab revolution. The rise of political Islam in Egypt, Turkey, Gaza and southern Lebanon coupled with the Islamic regime in Iran, has generated concern in Israel that it is again being surrounded by a ring of hostile states - in this case, Islamists rather than Arab nationalists. The article analyzes Israel's strategic thinking about the Middle East region. It looks at the importance of the "new periphery strategy" for Israeli efforts to advance the Arab-Israel peace process, and its potential role as the Arab Spring brings about greater Islamization of the Arab Middle East. Israeli strategic planners are talking of "spheres of containment" wherein countries like Cyprus, Greece, Azerbaijan, and Ethiopia constitute a kind of new periphery.